The study of miRNA-211 affects melanogenesis progress in Cashmere goats via suppressing AP1S2 - B. Zhang; R. Liu; T. Ma; X. Li; Y. Zhao; H. Su; J. Li; Y. Li; H. Jiang; Q. Zhang (Archives Animal Breeding)
Chromaticity is a key indicator of measuring economic worth of Cashmere goats, and gene regulation plays a major role in Cashmere goat color. By targeting the 3′UTR region of genes, such as miRNA-211, miRNA plays a significant regulatory role in melanogenesis. But the mechanism of how miRNA-211 affects the melanogenesis in Cashmere goats is unclear. As a result, insights into the color regulation by miRNA-211 in Cashmere goats and its brief mechanism are offered in this study. First, the target gene AP1S2 of miRNA-211 was screened by TargetScan and GO/KEGG, and then the targeted relationship was confirmed by the dual-luciferase reporter experiment. In B16-F10 cells, which overexpress miRNA-211 and goat skin, the opposite expression trends between AP1S2 and miRNA-211 were analyzed by reverse transcription–quantitative PCR (RT-qPCR) and western blot. And their opposite expression trends were confirmed in B16-F10 cells by immunofluorescence. The information above showed miRNA-211 downregulated the expression of AP1S2. Afterwards, the impact of miRNA-211 targeting AP1S2 on the melanogenesis of Cashmere goats was confirmed by animal regression studies. Utilizing immunohistochemistry, the expression of AP1S2 in a mouse hair follicle was observed. Following subcutaneous injection of antagomiRNA-211 (chemical modification inhibitor), the expression levels of the AP1S2 gene and protein were enhanced, and the localization in the hair follicle was also increased. Furthermore, reduction in melanin content in the skin was detected. These results showed that miRNA-211 significantly affected the melanogenesis progress via downregulating AP1S2 and advantageously affected the melanin content of Cashmere goat skin.